Program Bimbingan dan Konseling untuk Mencapai Kematangan Karir Siswa Sma Kartika Viii-1 - Sindi Nursalam; Herdi Herdi (Syntax Corporation Indonesia, 2023)
Career guidance is a significant type of guidance in SMA and MA. Career counseling is an effort to assist individuals in knowing and understanding themselves, learning about the world of work, and developing their future with the expected form of life. This study aims to describe the implementation of the guidance and counseling program in achieving career maturity for class XII students at SMA Kartika VIII-1, South Jakarta. This is very necessary to research because guidance and counseling services in secondary schools help students plan and develop their future careers. Descriptive technique with a quantitative approach, Thus, 38.7% is obtained in the high career decision-making category, 58.1% in the medium career decision-making category, and as much as 3.2% in the low decision-making category. According to data collected from 31 respondents, students' career maturity after the Science study program at SMA Kartika VIII-1 is as expected.